Structured illumination lensless digital holographic microscopy (SI-LDHM) - Zheng, Juanjuan; Guo, Xuhong; Ma, Ying; Wen, Kai; An, Sha; Wang, Xiaofang; Gao, Peng; Qian, Jiaming; Zuo, Chao; Gao, Peng (Frontiers in Physics, 2024)
In this work, we propose a structured-illumination lensless digital holographic microscopy (SI-LDHM). SI-LDHM illuminates a sample with 24 structured illuminations (8 orientations × 3 phase shifts) and records the defocused interferogram formed by two copies of object waves along the ±1 st diffraction orders of each SI. The reconstructed object waves under different illumination orientations are respectively propagated to the sample plane along the +1 st diffraction order and then averaged, thus yielding a clean image without the artifact of twin images. Experimental results demonstrated that thanks to the multi-oriented SI strategy, the twin image in SI-LDHM is sevenfold reduced compared to conventional DHM, while the spatial resolution is 1.15 times higher.